The Impact of Macroeconomic Variables on Jakarta Islamic Index (JII) Fluctuation - Maulana Ja'far Shodiq; Muhammad Ridho Al-Fathan; Muhammad Ridwan Hidayat (Review on Islamic Accounting, 2022)
This study aims to determine the impact of economic growth rates, inflation, interest rates, on prices or the level of JII price proportions. In addition, this study aims to determine how significant the influence of these factors is on the performance of the sharia-based stock market in Indonesia. The method used is multiple linear regression (OLS). The results of the study found that the economic growth rate has a significant positive effect on JII price and interest rates do not significant and negative effect.